Catchment size, soil type and land use to determine the amount and likelihood of flood in the Sarawak Corridor of Renewable Energy (SCORE) Region - Awang Abdillah, D.N.H; Selaman, O.S (Universiti Malaysia Sarawak (UNIMAS), 2009)
This study measures the likelihood of flood event by comparing the peak flow rates at the pre development and post development stages of the major system. The approach used is by the most common practice in hydrology that is Rational Method. With a higher peak flow rate obtained at post development stage, it has been proven that as more urbanization takes place, there is the more flood occurrence.